Taxing Sin Goods and Subsidizing Health Care (2012)
We study the taxation of sin goods in a two-period, three-good model. Individuals can buy health care to compensate for the damages caused by their earlier sin-good consumption. Individuals are myopic and underestimate the effect of the sinful consumption on health; in their second period, they may acknowledge their mistake or persist in their error. We characterize and compare the first-best and the (linear) second-best taxes in these different settings. In particular, we examine how the results are affected by the way sin-good consumption and health care interact in health production technology. © 2011 The editors of The Scandinavian Journal of Economics.